Intellectual innovative system for personalized support of tourist trips - Pasichnyk, V.; Savchuk, V. (Commission of Motorization and Energetics in Agriculture, 2016)
The main goal of the article is generalization of intellectual innovation project of information system “Mobile information assistant of the tourist” (MIAT), which provide a full-featured integrated information and technological support to tourists during planning and implementation stages of his journey using a wide range of modern information technologies. About two-thirds of today's tourists use information technology to plan and support their journey, while a significant number of them use mobile computer and telecommunications devices. The result of the research made by the group of researchers of the University “Lviv Polytechnic” is the project of innovative intelligent system “Mobile information assistant of a tourist” oriented on IT support of the user in planning and realization of his/her tourist trip in accordance with information technology slogan “EVERYTHING! HERE! IMMEDIATELY!!!”.
Keywords: tourist mobile application; tourism; location-based services; location-based recommendations; travel guide; route planning; navigation; indoor navigation; global positioning system; mobile technology